1991
DOI: 10.1159/000120588
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Hemorrhagic Stroke in Children

Abstract: The complications of hemorrhagic stroke in children begin first with one’s failure to establish the correct diagnosis or from the lack of knowledge of attendant phenomena and second, from those events which occur before, during or because of the treatment provided for specific lesions. The fundamental principles of history gathering, clinical evaluation and appropriate neuroimaging will direct safe, uncomplicated patient care. This paper will examine those complications which may arise during the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
1
7
1
Order By: Relevance
“…Unlike adults, children are less likely to make cerebral hemorrhage of hypertensive origins unless values are important and hypertension is associated with other risk factors such as sickle cell disease and arteritis [7]. Cardiac causes are also reported in significant proportions [4], which is not the case in our series.…”
Section: Evolutive Aspectscontrasting
confidence: 61%
See 2 more Smart Citations
“…Unlike adults, children are less likely to make cerebral hemorrhage of hypertensive origins unless values are important and hypertension is associated with other risk factors such as sickle cell disease and arteritis [7]. Cardiac causes are also reported in significant proportions [4], which is not the case in our series.…”
Section: Evolutive Aspectscontrasting
confidence: 61%
“…Our series of 13 cases in 11 years confirms the epidemiological reality. The cerebral hemorrhage can occur at all pediatric ages but with a peak between 5.6 years and 8.7 years (5.25) [5][6][7][8][9]. The average age of onset in our study was slightly higher with 9.85 years.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…As the child's skull was still growing, we decided to limit the skull opening to a standard pterional craniotomy with interfascial dissection as described by Yasargil and Fox [4]. The anterior clinoid was resected extradurally [5], which incidentally was not fully ossified. Intraoperative brain stem evoked potentials and somatosensory evoked potentials were used for monitoring.…”
Section: Case Reportmentioning
confidence: 99%
“…In a multicenter review of 1,289 patients, Hofmeister et al [1] reported a mean age at diagnosis of 31.2 years. The overall risk of hemorrhage from an untreated AVM in all age groups is estimated to be between 2 and 4% yearly [2,3,4]. Even though AVMs are rare in kids, estimated to represent 3% of all AVMs [5,6,7], they tend to rupture more frequently than in adults [5,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%